Sensory modulation deficits and anxiety symptoms in children receiving occupational therapy - Tauby, Michal Chava (My University, 2016)
This study aimed to identify the association between observable sensory behaviours and anxiety symptoms in school-aged children. The children were between the ages of 8-10 years and attended Remedial Schools. The participants were receiving occupational therapy and were identified as having a Sensory Modulation Disorder (SMD). Parents rated their children on the Sensory Profile, and scores were correlated to the Spence Children’s Anxiety Scale, completed by the children. Participants showed high quadrant scores indicating “low registration” and sensory “over-responsivity” (avoidance and sensitivity to sensory input). Further, the participants were identified to be an “at risk” population for anxiety disorders, as scores of elevated anxiety exceeded normal populations. Although total anxiety scores correlated with only avoidance quadrant scores (and not sensitive scores as predicted,) other scores indicating emotional behaviours correlated moderately with total anxiety scores. It is concluded that children with SMD are at risk of presenting with anxiety disorder symptoms, and must thus be monitored for these.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Occupational Therapy. Johannesburg, 2016
Keywords: Sensory Modulation Deficits; Child; Anxiety; Occupational Therapy